Screening over 100 000 patients in 39 general practices in the Netherlands for anticoagulation underprescription in atrial fibrillation: a descriptive, cross-sectional study - Freek Verheugt; Sander van Doorn; Martin E W Hemels; Ron Pisters; Leonard Voorhout; Constants H P H Geurts; Andrew Oostindjer; Harrie Rila; Wessel W Fuijkschot (BMJ Open)
Objectives To investigate the underprescription of oral anticoagulation (OAC) in individual atrial fibrillation (AF) patients in primary care.Setting Screening of patient records in 39 participating general practitioners (GPs) across the Netherlands.Participants We screened 101 207 patient records identifying 2375 non-valvular AF patients.Methods Using electronic patient files, we were able to screen the entire GP population for AF, CHA2DS2-VASc stroke risk scores, and the use of guidelines recommended OAC prescription. In case of a deviation from guidelines recommended OAC prescription, we checked the electronic patient file for any documented reason. Additionally, 6 weeks following the screening, we asked all GPs to provide information on any actions taken for the underprescribed patients.Results We found a mean CHA2DS2-VASc score of 3.2. OAC prescription consisted of direct OAC in 1342/1984 (68%) and vitamin K-antagonists in the remainder of patients. OAC underprescription was present in 93/944 (9.9%) females and 101/1374 (9.7%) in males, respectively. In 111/146 (76.0%) of the underprescribed AF patients, no reason to withhold OAC was reported. Reported reasons to withhold OAC were patient refusal (n=10), cardiologist advice (n=7) and high risk of bleeding (n=7). Data regarding actions following the identification of OAC underprescription were available for 92/194 (47%) of the OAC underprescribed cases. After consultation OAC was initiated in 9/92 (10%) only.Conclusions In this large Dutch study among GPs, we observed 9.8% underprescription of OAC in AF patients. In 76% of the AF patients lacking a prescription for OAC, no documentation for deviating from the guidelines was found. Only in a minority of cases detection of OAC underprescription lead to OAC initiation.